2021
DOI: 10.1088/1742-6596/2083/3/032067
|View full text |Cite
|
Sign up to set email alerts
|

Energy Storage Technology Used in Smart Grid

Abstract: Energy storage is one of the main problems bothering the power system. The present research situation of energy storage is outlined. The working principles, development process and technical features of pumped storage, compressed air energy storage, flywheel energy storage, electromagnetic energy storage and chemical energy storage are described in detail. The application prospect of energy storage is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The distinction between high-energy and high-power storage solutions highlights their versatility in meeting diverse energy demands across different scales and applications. The effective deployment of these technologies enhances grid reliability and efficiency by addressing the varied energy needs of residential and utility-scale contexts [11][12][13][14]. The second category concerns high-power storage technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction between high-energy and high-power storage solutions highlights their versatility in meeting diverse energy demands across different scales and applications. The effective deployment of these technologies enhances grid reliability and efficiency by addressing the varied energy needs of residential and utility-scale contexts [11][12][13][14]. The second category concerns high-power storage technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a plethora of research has focused on the development of effective catalysts to improve the selectivity and Faradic e ciency (FE) of NH 3 or aimed at studying intrinsic mechanisms by exploring new characterization techniques [1][2][3][4][5][6][7][8] . Excitingly, as a sustainable alternative to traditional thermal and enzymatic catalysis, coupling inorganic nitrogen sources (e.g., nitrogen (N 2 ), NO 3 − , NO 2 − ) and carbon sources (e.g., carbon dioxide, carbon monoxide, and other carbonyl substrates) to form upgraded organic amines is becoming a rapidly emerging area of electrocatalytic C − N bond construction, pushing NO 3 − /NO 2 − electroreduction to a new level due to the frequent invocation of C − N construction in synthetic chemistry [9][10][11][12][13][14][15] . For example, Wang et al reported electrocatalytic C − N coupling to successfully synthesize methylamine from CO 2 and NO 3 − catalyzed by a well-designed molecular cobalt catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the collection, transport, storage, and usage of NH 3 are timeand manpower-consuming processes that require high costs and complex handling and cause safety risks owing to its pungent property. Inspired by recent advances in electrochemical C − N coupling based on inorganic nitrogen sources, [9][10][11][12][13][14][15][16][17] we propose to explore a highly promising and sustainable method by integrating NO 3 − /NO 2 − electroreduction to NH 3 with cascade metal-catalyzed cross-coupling of NH 3 with arylboronic acids to form arylamines, which remain untouched up to now. One key issue is that homogeneous metal complexes for the C − N coupling step must be added, and most metal complexes are easily reduced to zero valence metals under cathodic conditions for NO 3 − /NO 2 − reduction, leading to their deactivation for C − N coupling.…”
Section: Introductionmentioning
confidence: 99%